INVENTARISASI PERMUDAAN BAKAU (Rhizophora spp.) DI WILAYAH KELOLA KPH UNIT V BENGKALIS PROVINSI RIAU - Aprianto Pranata Yosua; Yossi Oktoini; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Rhizophora spp. is one of the mangrove tropic plant from Rhizospora, family Rhizophoraceae. This plant has specific like huge root and wooden, at the top close with the leaves, and fruit that grow in the trees. The limitation about the data available and value of jouvenile, give want to do research. The aimed of this research is to know availability, value, and dominance mangrove regeneration (Rhizospora spp.) in area managed by KPHP unit V Bengkalis regency, Riau Province. The method that used in this research is design sampling. The result showed that seedling level INP 109,83% with intensity 1.816,98 seedling/ha, sapling level INP 106,82% with intensity 429,38 sapling/ha, poles level bakau INP 91,66% with intensity 30,26 poles/ha and trees found 4 species, with all number of tree in a plot that inventory is 444 trees. Regeneration plant dominance by Mangrove INP 181,02%. Keywords: Inventaritation, Mangrove (Rhizospora spp.), KPHP, INP